Addition of Glodokan Tiang Leaf Flour( Polyalthia Longifolia ) In the Diet on the growth of broiler chickens - Sumadja, Wiwaha Anas; Hani, Siti Fitra (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2023)
Polyalthia longifolia is a plant from India. Â In Indonesia, it is often called glodokan tiang which is one of the most popular plants with tall trees grows tall, has short branches. This plant contains several compounds such as alkaloids, steroids, tannins, saponins which can increase growth and feed efficiency, as well as improve the quality of livestock meat , flavonoids which is useful as an appetite enhancer, reducing feed intake, and increasing pigment. This study aims to determine the effect of the addition of leaf flour Polyalthia longifolia in the ration on the growth of broiler chickens. This research was conducted at the Farm Faculty of Animal Husbandry, University of Jamb for 5 weeks. This study used 200 DOC. The treatments given were P0 (the ration contains 0% leaf flour Polyalthia Longifolia ), P1 (the ration contains 1% leaf powder Polyalthia Longifolia ), P2 (the ration contains 2% leaf powder Polyalthia Longifolia ) and P3 (the ration contains 3% leaf powder Polyalthia Longifolia ). This study used a completely randomized design (CRD) with 4 treatments and 5 replications. The data collected were subjected to analysis of variance. The study's findings revealed the treatment had no significant (P > 0.05) influence on consumption ration, body weight gain, or ration conversion. It may be concluded that the addition of Polyalthia longifolia leaf flour to the diet up to 3% had no negative influence on ration consumption, body weight gain, or ration conversion.